The impact of COVID vaccination on incidence of long COVID and healthcare resource utilisation in a primary care cohort in England, 2021–2022 - Jingyan Yang; Kiran K. Rai; Tamuno Alfred; Lucy Massey; Olivia Massey; Leah McGrath; Kathleen M. Andersen; Theo Tritton; Carmen Tsang; Rebecca Butfield; Charlie Reynard; Diana Mendes; et al. (BMC Infectious Diseases)
Abstract Background Long COVID, a diverse set of symptoms that persist after a minimum of 4 weeks from the initial SARS-CoV-2 infection, has posed substantial burden to healthcare systems. There is some evidence that COVID-19 vaccination may be associated with lower risk of long COVID. However, little is known about the association between vaccination status and long COVID-associated healthcare resource utilisation (HCRU) and costs. Methods We conducted a cohort study using primary care electronic health record data in England from the Clinical Practice Research Datalink (CPRD) Aurum dataset linked to Hospital Episode Statistics where available. Adult (≥ 18 years) patients were indexed on a COVID-19 diagnosis between 1st March 2021 and 1st December 2021. Vaccination status was assessed at index: unvaccinated or completed primary series (two doses for immunocompetent and three doses for immunocompromised patients). Covariate balance was conducted using entropy balancing. Weighted multivariable Poisson regression was used to estimate the incidence rate ratio (IRR) for incident long COVID, and separately long COVID primary care resource use, by vaccination status. Patients were followed up to a maximum of 9-months post index. Results A total of 35,713 patients who had completed primary series vaccination, and 75,522 unvaccinated patients were included. The weighted and adjusted IRR for long COVID among patients vaccinated with the primary series compared to being unvaccinated was 0.81 (95% CI: 0.77–0.86) in the overall cohort, 0.83 (95% CI: 0.78–0.88) in the immunocompetent cohort and 0.28 (95% CI: 0.13–0.58) in the immunocompromised cohort. Among those with long COVID, there was no association between the rate of primary care consultations and vaccination status in the overall and immunocompetent cohorts. Cost of primary care consultations was greater in the unvaccinated group than for those who completed primary series. Conclusion Vaccination against COVID-19 may reduce the risk of long COVID in both immunocompetent and immunocompromised patients. However, no association was found between frequency of primary care visits and vaccination among patients diagnosed in 2021. Future studies with larger sample size, higher vaccine uptake, and longer study periods during the pandemic are needed to further quantify the impact of vaccination on long COVID.